USING HYPNOTEACHING TECHNIQUE TO IMPROVE THE STUDENTS’ VOCABULARY MASTERY - Action Research at Second Grade of SMAN 5 Kendari - La Ode Muhammad Idrus Hamid B. (Journal of English Education, 2016)
The objective of this research was to improve the students’ vocabulary mastery through hypnoteaching. It was a mixed research with action research method in SMAN 5 Kendari. The research data were taken in the first semester of SMAN 5 Kendari with 28 students and analyzed qualitatively and quantitatively. The data were collected through observation and vocabulary test. The data analysis and interpretation indicated that there is an improvement in students’ vocabulary mastery. Quantitatively, it was found that the students’ vocabulary mastery increased significantly from the first until second cycles. Therefore, it concluded that the students’ vocabulary mastery can be improved by using hypnoteaching. The finding leads to the recommendation for the teachers to use hypnoteaching as an alternative technique in teaching vocabulary. It also recommended to other researchers to continue research.